Hyperthyroidism as a Precipitant Factor for Cerebral Venous Thrombosis: A Case Report - Ahmed Elkhalifa Elawad Elhassan MBBS; Mohammed Omer Khalil Ali MBBS; Amina Bougaila MD; Mohammed Abdelhady MBBCH, EDiR; Hassan Abuzaid MBBS, MD, FRCP (Edin) (SAGE Publishing, 2020)
Cerebral venous sinus thrombosis (CVT) is an uncommon yet serious condition. While CVT has many known precipitants and etiologies, hyperthyroidism as a precipitant of CVT is not well understood. This study reported a case of a 41-year-old male with a 4-year history of hyperthyroidism presented with seizure. Consequently, a diagnosis of superior sagittal sinus thrombosis was confirmed by computed tomography and magnetic resonance (MR) venograms. Extensive investigations yielded no apparent underlying cause, but laboratory findings were consistent with uncontrolled hyperthyroidism. The patient improved rapidly following anticoagulation. Follow-up MR and MRV scans 2 months after treatment revealed full recanalization of the superior sagittal sinus. This case report highlighted hyperthyroidism, as a procoagulant condition, resulting specifically in superior sagittal sinus thrombosis.